Impact of confinement resulting from Covid 19 on Quality of Life, Mental Health and Psychological Well Being in Higher Education Students in Santarém and Leiria - Silva, Mário Ribeiro da (2021)
Background: The coronavirus context in higher education disrupted students' lives. Restrictions on social mobility and the consequent reduction in interpersonal contacts brought unprecedented stressful situations, as well as marked changes in their daily lives, challenging the feeling of loneliness and the very perception of social isolation, with consequences on their quality of life. Methods: A cross-sectional descriptive study was carried out. Participants were 775 students, aged between 17 and 55 years, aiming to describe the self-perception of the evaluated mental health dimensions by the Anxiety, Depression and Stress Scales; the Psychological Well-Being by the Manifestation of Psychological Well-Being Measure Scale and to evaluate the quality of students' lives by WOOQOL-Bref. Collected data were analyzed with IBM SPSS Statistics for Windows software, Version 27.0. Results: The results obtained, in the global sample considered, revealed that the lowest average corresponds to anxiety (0,52 ± 0.76), followed by depression (0,67 ± 0,96) and stress (0,90 ± 0,87). Regarding psychological well-being, the lowest average corresponds to social involvement (2,39 ± 1,10), followed by happiness (2,91 ± 1,22), self-esteem (2,9 5 ± 0,91), control of self and events (2,96 ± 0,97), mental balance (2,97±1,14) and sociability (3,21±1,13). Regarding the quality of life, between the social relationship’s domain (52,71 ± 19,10) and the environment domain (53,92±10,48), there were no statistically significant differences. The highest mean value occurred in the physical domain (64,87±12,54) and the lowest in the psychological one (49,60 ±16,18). We also found significant differences in terms of polytechnic institute attended and gender. Conclusion: The obtained results provide the basis to design and develop a targeted intervention main program focused on the empowerment of higher education students. Build a literacy program with health education strategies, starting from their own perceptions and responses to the experienced situations.